INTERVENTION PLAN FOR EXPANDING VACCINATION COVERAGE IN THE FAMILY HEALTH STRATEGY VII DR. ALEX BOREM, MUNICIPALITY OF CAPITÃO ENÉAS-MG - Garrido, Emílio Maurício Fernandez; Borges, Carina Barbosa; Baracho, Valéria da Silva; Ferreira, Taysa Sant Ana; Carvalho, Liliany Mara Silva; Ribeiro, Liliane da Consolação Campos; Barroso, Heloisa Helena; da Silva, Natália Cristina; da Cruz, Paulo Henrique Ferreira (Seven Editora, 2026)
Introduction: Vaccines are one of the most effective mechanisms in defending the human body against infectious and bacterial agents, and consist of protecting the body through resistance to diseases that would affect it. They are composed of inactivated or attenuated substances and microorganisms that are introduced into the body to stimulate the immune system’s reaction when in contact with a diseasecausing agent. In the health unit where I work, we noticed the low vaccination coverage in adults and the elderly. So we decided to work on this topic in the Intervention Project. Objective: Develop an intervention plan to increase routine vaccination coverage of the national immunization plan, in the Family Health Strategy: Dr Alex Borém from the municipality of Capitão Eneas. Methodology: The use of Situational Strategic Planning (PES) which proposes to identify and intervene on the population’s health problems. To systematize the action plan, a meeting will be held with the municipality’s Health Surveillance and Primary Care coordinator to present the action plan and then a meeting with the multidisciplinary team involved in developing the actions at UBS VII. Alex Borém. After this, we will try to make a diagnosis of which vaccines are necessary and which patients need to receive immunization. All members of the healthcare team will be encouraged to participate, by calling users, in any type of service provided by us. Users will be invited through active search, during home visits and through message groups in which neighborhood users are included, or at any appearance at the health unit. Expected Results: It is expected that, at the end of the implementation of this intervention plan, users registered at the Dr. Alex Borém Basic Health Unit, in the municipality of Capitão Enéas (MG), will present their vaccination cards duly updated in accordance with the National Immunization Calendar, covering ages from childhood to the elderly population. It is planned to carry out a survey of 100% of the mirror cards to compose the situational diagnosis of the territory’s vaccination coverage, enabling more targeted and effective planning of actions. With this intervention project, it is expected that the population of the area will have easier access and we will thus be able to increase vaccination coverage to close to 95% of patients assisted by the Family Health Strategy Dr Alex Borém Município Capitão ênea MG. Final considerations: Emphasize that, although interventions can be successful in specific contexts, a systemic and continuous effort is necessary to address the multiple factors that influence vaccination coverage and guarantee collective health in the long term.